Юридичні технології підтвердження чинності документів у приватній та публічній сферах - Чередник Роман Вікторович; Чередник Р. В.; Cherednyk R. V. (My University, 2025)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.01 – теорія та історія держави і права; історія політичних і правових учень. – Національний університет «Одеська юридична академія», Одеса, 2025. У дисертаційному дослідженні здійснено загальнотеоретичне обґрунтування засад використання юридичних технологій підтвердження чинності документів у приватній і публічній сферах, визначення їх ролі в сучасному праві. Обґрунтовано, що удосконалення процедур підтвердження чинності документів є одним з ключових завдань, виконання якого забезпечує функціонування сучасної держави. Правовідповідні алгоритми встановлення валідності правових актів формують опорну інфраструктуру для цифрового правопорядку, підвищують ефективність правового регулювання. У зазначеному аспекті наявність якісних юридичних технологій підтвердження чинності документів створює умови для забезпечення окремих вимог післявоєнного відновлення нашої держави, подальшої європейської інтеграції та гармонізації правового простору, врахування викликів цифрової трансформації у сфері державного управління.

Визначено, що на внутрішньодержавному рівні підтвердження чинності документів здійснюється у таких формах: державна реєстрація нормативно правових актів, легалізація доказів, нотаріальне підтвердження чинності документів (публічний нотаріат), підтвердження чинності документів уповноваженими особами.

Зовнішньодержавний рівень включає: апостилювання, консульську легалізацію та визнання іноземних документів про освіту (нострифікацію). Запропоновано використання юридичних технологій підтвердження чинності документів та здійснено їх класифікацію, згідно з якою слід виокремлювати загальні та спеціальні юридичні технології.

Здійснено порівняльно-правовий аналіз процедур підтвердження чинності документів за законодавством країн романо-германської правової сімї та у провідних країнах сім’ї загального права. На підставі міжнародного досвіду зроблено висновки про напрями удосконалення процедур підтвердження чинності документів в Україні.

The thesis stands for a Candidate degree in Law, speciality 12.00.01 – theory and history of state and law; history of political and legal doctrines. – National University «Odesa Law Academy», Odesa, 2025. A theoretical generalization of the concept of legal technologies for confirming the validity of documents in the public and private spheres was carried out in the thesis. It is determined that the confirmation of the validity of documents takes place in public-legal and private-legal spheres and reflects the general trend of differentiation of legal regulation depending on the nature of legal relations and is not only theoretically justified, but also practically necessary. Therefore, in the public legal sphere, the legal force of the document is guaranteed at the state level, especially with regard to foreign state circulation. The private law sphere is aimed at ensuring flexibility and efficiency in servicing private legal relations. At the same time, there is a functional interaction between these spheres – documents, the validity of which is confirmed in the private law sphere, often require confirmation in the public sphere in order to fully realize their legal force. The external state level includes: apostillization, consular legalization and recognition of foreign documents on education (nostrification).

The use of legal technologies for confirming the validity of documents is proposed and their classification is carried out, according to which it is necessary to allocate: 1) general legal technologies: technology of conceptual assessment of a document, technology of system-legal assessment, technology of legal-technical assessment; 2) special legal technologies: the technology of content analysis of the document (determining the legal nature of the document, establishing the legality, formal-logical analysis, legal-hermeneutical analysis), the technology of formal analysis of the document (establishing compliance with structural rules, establishing compliance with requisite and procedural rules and linguistic analysis) and legal technologies for formalizing the results of verification of the validity of the document (preparation of a certified inscription, registration and accounting, as well as issuing a document with certifying elements).

A comparative legal analysis of procedures for confirming the validity of documents under the legislation of Western European countries such as France, Germany and the Netherlands, has been carried out. An increase in the role of private law aspects in the sphere of confirmation of the validity of documents was elicited in the thesis, which reflects not only current trends in legal development, but also deep historical traditions of the continental legal system based on Roman law.

Features of confirmation of the validity of documents in the countries of the common law family are established. In general, the Anglo-American approach is based on customs and precedents formed by legal practice, and not on codified legal norms. In this system, the main purpose is to certify signatures on documents, confirming their reliability and compliance with legal requirements, which indicates compliance with formal analysis. At the same time, the use of legal technologies relating to content analysis in common law countries is usually carried out by lawyers who, representing the interests of clients, challenge the provisions of legal documents in court proceedings. On the basis of international experience, conclusions have been drawn on the directions of improving the procedures for confirming the validity of documents in Ukraine.
Чередник Р. В. Юридичні технології підтвердження чинності документів у приватній та публічній сферах : дис. ... канд. юрид. наук / Роман Вікторович Чередник ; Національний університет "Одеська юридична академія". - Одеса, 2025.
Keywords: апостиляція; консульська легалізація; легалізаційна діяльність; нострифікація; підтвердження чинності документів; правова система; правові тенденції; правовідповідність; правозастосування; правова процедура; удосконалення права; універсалізація; юридична діяльність; юридичні технології; юридичний документ; apostillization; consular legalization; legalization activity; nostrification; confirmation of the validity of documents; legal system; legal trends; legal compliance; law enforcement; legal procedure; improvement of law; universalization; legal activity; legal technologies; legal document